2016
DOI: 10.1111/ijfs.13238
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic preparation of immunomodulatory hydrolysates from defatted wheat germ (Triticum Vulgare) globulin

Abstract: Summary Defatted wheat germ globulin (DWGG) was hydrolysed using the enzymes alcalase, neutrase, papain, pepsin or trypsin to improve the immunomodulatory effects of the protein. The degree of hydrolysis (DH), molecular weight distribution, hydrophobicity, secondary structures and immunomodulatory activities were determined. The DH of hydrolysate using alcalase or neutrase was higher (P < 0.05) than that of hydrolysate prepared by other proteases. Alcalase hydrolysate (AH) had the strongest (P < 0.05) immunomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 34 publications
2
29
2
Order By: Relevance
“…The type of protease used may influence the DH as well as the bioactivity of hydrolysates. Wu et al () recently reported that an Alcalase hydrolysate of defatted wheat germ globulin had a higher DH compared with hydrolysates produced using papain or pepsin, and the Alcalase hydrolysate had significantly greater immunomodulatory activity in RAW264.7 cells. Karamac, Kosinska‐Cagnazzo, and Kulczyk () reported that an Alcalase hydrolysate of flaxseed protein had higher antioxidant activity compared to hydrolysates produced using papain or other proteases such as trypsin and flavourzyme.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The type of protease used may influence the DH as well as the bioactivity of hydrolysates. Wu et al () recently reported that an Alcalase hydrolysate of defatted wheat germ globulin had a higher DH compared with hydrolysates produced using papain or pepsin, and the Alcalase hydrolysate had significantly greater immunomodulatory activity in RAW264.7 cells. Karamac, Kosinska‐Cagnazzo, and Kulczyk () reported that an Alcalase hydrolysate of flaxseed protein had higher antioxidant activity compared to hydrolysates produced using papain or other proteases such as trypsin and flavourzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Casein hydrolysates containing hydrophobic amino acids, such as leucine and proline, have also been reported to have antiinflammatory activity in cells (Malinowski, Klempt, Clawin-Rädecker, Lorenzen, & Meisel, 2014). Wu et al (2016) reported that higher levels of hydrophobic amino acids in hydrolysates of defatted wheat germ globulin were linked to higher immunomodulatory activity in RAW264.7 cells. Deer antler protein, which was hydrolyzed to generate potent anti-inflammatory hydrolysates, was reported to contain high quantities of glutamic acid, glycine, proline, and leucine (Zhao, Wang, Zhang, & Xie, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Identification of molecular mass and amino acid sequences of purified peptides (fraction A3-B3-C2-D1-1) by HPLC-ESI-Q-TOF MS system. correlate with immunomodulatory activity (Wu et al, 2016), which may increase the interaction of the peptide and cytomembrane and so improve immunomodulation (Mercier, Gauthier, & Filiss, 2004). In addition, being rich in basic amino acids or hydrophobic amino acids in terminals is also related to immunomodulatory activity (Chen, Muramoto, & Yamauchi, 1995).…”
Section: Identification Of Amino Acid Sequence Of Immunomodulating Pementioning
confidence: 99%
“…It is widely used in a range of food (bakery products) as well as non‐food applications which includes production of bioplastics (Langstraat et al ., ) through to animal feeds and adhesives (Day et al ., ). Gluten can be hydrolysed to produce bioactive peptides with anti‐oxidant, anti‐microbial, anti‐cancer, opioid or anti‐hypertensive activities (Korhonen & Pihlanto, ; Shahidi & Zhong, ; Zhu et al ., ; Janković et al ., ; Garg et al ., ; Wu et al ., ). Enzymatic hydrolysis is the preferred method for the production of bioactive peptides and the extent of hydrolysis depends on the number, nature of amino acids and their sequence.…”
Section: Introductionmentioning
confidence: 97%